The Role of Regular Exercise in Improving Body Immunity: A Literature Review - Azmi, Dwi (PT. Anagata Sembagi Education, 2025)
This study aims to examine the role of regular exercise in improving body immunity through a qualitative approach based on literature studies. The background of this study is based on the increasing public awareness of the importance of body immunity after the COVID-19 pandemic and the need for effective and affordable non-pharmacological health strategies. Data were obtained from various relevant scientific journals and academic books, then analyzed using the content analysis method. The results of the study indicate that moderate-intensity exercise carried out routinely can increase the activity of immune cells such as lymphocytes, macrophages, and natural killer (NK) cells, as well as balance the production of pro- and anti-inflammatory cytokines. In addition, exercise also has a positive impact on reducing stress and improving sleep quality, two important factors that support the immune system. However, excessive exercise can reduce the immune response and increase the risk of infection, so the intensity and duration of exercise need to be considered. This study confirms that regular exercise is an effective preventive strategy and needs to be integrated into everyday life as part of a healthy lifestyle. These findings can be a reference for the formulation of promotive policies in the field of public health.